The Modern Sources of Anthropocentrism. Part two - Ganowicz-Bączyk, Anita (Studia Ecologiae et Bioethicae, 2011)
Anthropocentrism seems to be a fundamental notion concerning the man-nature relation. ?e anthropocentric attitude is largely meant to be the main cause of the ecological crisis. One can distinguish at least several stages of the process, which led to this crisis, namely: stage of Magic and Myth, Ancient Times, Middle Ages, and Modern Times. The aim of this article is to show the process of development of an anthropocentric thought in Modern European culture when the culmination of this process is observed. Among the causes of the modern worldview, one can mention e.g. the modern conception of science, technology development, as well as social, political, and cultural changes. Contemporary view on nature and man was influenced not only by mechanistic and materialistic theories tending to subordinate nature to man (G. Bruno, F. Bacon, R. Descartes) but also by philosophical views which on the one hand excluded man from nature (I. Kant) and on the other made attempts to restore man to nature (J. J. Rousseau, F. W. J. Schelling).